Clinical and laboratory findings in twins with neonatal epileptic encephalopathy mimicking aromatic L-amino acid decarboxylase deficiency - Bräutigam, Christa; Hyland, K.; Wevers, R.; Sharma, R.; Wagner, L.; Stock, G.-J.; Heitmann, F.; Hoffmann, Georg F. (Neuropediatrics, 2002)
Thieme E-Books & E-Journals
Gesehen am 28.12.2020